Activation mechanism of lead ions in the flotation of sphalerite depressed with zinc sulfate. (15th January 2020) - Wang, Han; Wen, Shuming; Han, Guang; Xu, Lei; Feng, Qicheng
Graphical abstract: Highlights: Flotation recovery of ZnSO4 -depressed sphalerite was significantly increased after treatment with lead ions. A greater amount of xanthate species adsorbed on the lead-treated surface of ZnSO4 -depressed sphalerite. O atoms on the ZnSO4 -depressed sphalerite surface were primary reactive sites for adsorption of lead species. An adsorption layer of activated products on the ZnSO4 -depressed sphalerite surface was observed by ToF-SIMS. Abstract: Sphalerite is commonly associated with other metal-sulfide minerals, and is usually depressed with zinc sulfate (ZnSO4 ) prior to the preferential flotation of other sulfide minerals with excellent floatability. In subsequent processing, ZnSO4 -depressed sphalerite activation is necessary for the maximum recovery of zinc resources. In this work, lead nitrate (Pb(NO3 )2 ) was used to activate the depressed sphalerite surface by zinc sulfate (ZnSO4 ). The lead-ion activation mechanism was studied in the flotation of ZnSO4 -depressed sphalerite through microflotation tests, zeta-potential experiments, local electrochemical impedance spectroscopy, X-ray photoelectron spectroscopy, and time-of-flight secondary ion mass spectrometry. Floatability of ZnSO4 -depressed sphalerite after treatment with Pb(NO3 )2 improved significantly and the maximum recovery reached 96.4%. The zeta potential, local electrochemical impedance spectroscopy, X-ray photoelectron spectroscopy outcome displayed lead species could adsorb on the Zn-depressed sphalerite surface as Pb 2+ and Pb(OH) + and form –Zn–O–Pb complexes, which enhanced the active sites at mineral surfaces significantly, promoted xanthate species attachment to the depressed minerals surface, and enhanced mineral-particle hydrophobicity. The adsorption layer of activated products on the ZnSO4 -depressed samples surface was represented by ToF-SIMS, which illuminated its activation mechanism further.